Interfacial field-driven self-poling in a lead-free P(VDF–TrFE)/BCZT nanogenerator: achieving high-performance energy harvesting via percolation-optimized dielectric coupling - Ukasi, Sirinya; Triputtikun, Jakkrit; Sae-tang, Chanachot; Sumang, Rattiphorn; Panpho, Phakakorn; Rattanawongwiboon, Thitirat; Hajra, Sugato; Kim, Hoe Joon; Vittayakorn, Wanwilai; Charoonsuk, Thitirat; Vittayakorn, Naratip (My University, 2026)
Achieving spontaneous dipole alignment without external poling remains a grand challenge in developing high-performance ferroelectric nanogenerators. This work reports a self-poling mechanism driven by engineered interfacial fields at the polymer–ceramic junction. By embedding lead-free Ba0.85Ca0.15Zr0.1Ti0.9O3 (BCZT) crystals into a P(VDF–TrFE) matrix, we create strong localized electric fields that promote unidirectional dipole orientation, thereby eliminating the need for conventional electrical poling procedures. The resulting hybrid piezo-triboelectric nanogenerator (H-PTENG), optimized at a 1 wt% BCZT loading, exhibits remarkable energy-harvesting performance with a high open-circuit voltage (∼173.4 V), short-circuit current (∼5.23 µA), and power density (∼182 µW cm−2), outperforming most lead-free counterparts. This dielectric percolation-like optimum maximizes the dielectric–ferroelectric coupling mediated by Maxwell–Wagner–Sillars interfacial polarization, simultaneously enhancing piezoelectric and triboelectric outputs while preserving low dielectric loss. The device also demonstrates robust mechanical durability (>10 000 bending cycles) and retains usable output under varying humidity and temperature conditions, although its performance is reduced at ultra-high relative humidity due to water-induced charge dissipation. Its real-world applicability is confirmed by directly powering commercial electronics, including 82 LEDs, a digital wristwatch, an electronic scoreboard, and a Bluetooth-enabled humidity–temperature sensor. Collectively, this work establishes a scalable, lead-free, and poling-free design paradigm based on interfacial field engineering for next-generation flexible, self-powered electronic systems.